2014
DOI: 10.1089/ees.2013.0436
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Poly(acrylonitrile) Electrospun Ion-Exchange Fibers

Abstract: A potential ion-exchange material was developed from poly(acrylonitrile) fibers that were prepared by electrospinning followed by alkaline hydrolysis (to convert the nitrile group to the carboxylate functional group). Characterization studies performed on this material using X-ray photoelectron spectroscopy, scanning electron microscopy, Fourier-Transform infra-red spectroscopy, and ion chromatography confirmed the presence of ion-exchange functional group (carboxylate). Optimum hydrolysis conditions resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…a high‐molecular‐weight hydrophilic polymer or inorganic sol) is necessary. Secondary functionalization of the electrospun neutral nanofibers is another way to prepare ion‐exchange nanofibers . For example, Matsumoto et al investigated the preparation of cation‐ and anion‐exchange mats by first electrospinning polystyrene and poly(4‐vinylpyridine) solutions followed by sulfonation of the polystyrene mats and quaternization of the poly(4‐vinylpyridine) mats .…”
Section: Fundamental Aspects Of Ion‐exchange Nanofibersmentioning
confidence: 99%
“…a high‐molecular‐weight hydrophilic polymer or inorganic sol) is necessary. Secondary functionalization of the electrospun neutral nanofibers is another way to prepare ion‐exchange nanofibers . For example, Matsumoto et al investigated the preparation of cation‐ and anion‐exchange mats by first electrospinning polystyrene and poly(4‐vinylpyridine) solutions followed by sulfonation of the polystyrene mats and quaternization of the poly(4‐vinylpyridine) mats .…”
Section: Fundamental Aspects Of Ion‐exchange Nanofibersmentioning
confidence: 99%
“…It has been reported that the -COOH groups introduced by functionalizing electrospun poly(acrylonitrile) fibers for ion-exchange applications [28] or poly(methacrylic acid) grafted starch nanoparticles get ionized and develop a negative charge at high pH or physiological pH [33]. Also, DOX ionizes at physiological pH and develops a positive charge [26].…”
Section: Discussionmentioning
confidence: 99%
“…Poly(ε-caprolactone) (PCL) is a biodegradable, aliphatic polyester that has found application in various fields such as drug delivery systems, medical devices, tissue engineering and it has been shown that the surface functionality of sub-micron sized electrospun PCL fibers could be enhanced through different functionalization techniques such as hydrolysis, and aminolysis [27] The hydrolysis of PCL results in incorporation of carboxylic acid groups that could be ionized to develop a negative charge at alkaline pH [28] and as stated earlier, DOX gets ionized at alkaline pH to develop a positive charge. Herein, we hypothesize that the ionization of the functional groups on hydrolyzed PCL fiber surface and DOX can be used to form ionic bonds between the two as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The 0.2 μm pore sized fibrous PAN substrates were first hydroxylated via immersion in 1 M KOH for 30 minutes at 70 ℃ . This was done to enhance a negative charge via the conversion of the nitriles in the PAN substrates to carboxylic groups [39,41,42]. Subsequently, the substrates were rinsed with distilled water and dried prior to immersion in a positively charged 2.0 mg/ml PEI solution for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%